Efficient Market Hypotheses of Nepalese Stock Market - Dhodary, Shanker (Pravaha, 2020)
The purpose of this paper is to examine the random walk hypothesis (RWH) by testing the weak-form efficiency in the Nepalese capital market. Descriptive, correlation and causal comparative research design has been used for analyzing the variables and different phenomenon. This research has been prepared only with the help of secondary data. Closing price of company has been collected and analyzed for the period 2015/16-2019/20. Thus researcher tried to analyze the market efficiency with the help of five years data (daily closing price).There are altogether around 233 companies listed in NEPSE. So to make this research feasible and simple researcher has selected only 10 companies from the NEPSE by using purposive sampling technique. In course of selecting company researcher has tried to incorporate only financial sectors as commercial banks, finance companies, insurance, and microfinance companies but development bank has not been taken as sample due to same nature of commercial bank. Researcher examined the weak form efficiency of the Nepal stock exchange (NEPSE) using auto correlation test (parametric test) and run test (non-parametric test) for the period of 2015/16-2019/20. Mainly this research work tested the efficient market hypothesis of Nepalese stock market with the help of daily closing price of 10 Sample Company of different sectors. The market is inefficient in the weak form implies that the NEPSE does not follow a random walk. This means that the NEPSE provides an opportunity for out- performance by skillful managers and investment specialists. Auto correlation exists in price of stock evident that there is high level of dependency of price of stock with the previous ones. It will be easy for speculator and trader to exploit the market and gain handsome profit from the market. All investor are not assumed to be rational in inefficient market, most of the people say investor are investing on the basis of market rumor. Market may be inefficient due the asymmetric of information and insider trading.